Geotechnical study and evaluation of the PT. Dizamtra Powerindo, West Merapi District, Lahat Regency, West Sumatra Province - Abdul Jalil; Barlian Dwi Nagara; Eko Wicaksono (ReTII, 2022)
Determination of an acceptable slope angle in open pit mines is a key aspect of mine design, as it implies finding the optimal balance between economic benefits and mining risks. Mining activities will cause changes in the stress distribution on the slopes which can lead to landslides. This geotechnical study aims to provide recommendations on the design of mine slope openings, perform FK Life of Mine (LOM) calculations at PIT-1, PIT-2, PIT-3, PIT-3, PIT-4, PIT-5 north and south., is done by calculating the existing primary and secondary data, so that the results obtained are a real value on the object. This quantitative method is carried out by direct testing both in the field and in the laboratory, such as RQD, RMR, and GSI. To calculate the FK value using the limit equilibrium method. The results of the analysis of the southern FK LOM at PIT-1 1.539, PIT-2 1.536, PIT-3 1.68, PIT-4 1.502, PIT-5 1.493, North FK LOM PIT-1 2.522, PIT-2 1.98, PIT-3 2.29, PIT-4 1996, PIT-5 2,964.